Interleukin-21 accelerates thymic recovery from glucocorticoïd-induced atrophy. - Moutih Rafei; Maude Dumont-Lagacé; Alexandre Rouette; Claude Perreault (PLoS ONE, 2013)
Both physiological and psychological stress cause thymic atrophy via glucocorticoïd (GC)-dependent apoptosis of double-positive (DP) thymocytes. Given the pervasiveness of stress, GC-induced thymic atrophy is arguably the most common type of acquired immunodeficiency. We recently reported that interleukin-21 (IL-21) has a unique ability to expand the small subset of DP thymocytes (CD69(+)) which are ongoing positive selection, and that administration of IL-21 increases thymic output in aged mice. The goal of this study was to evaluate whether IL-21 could mitigate GC-induced thymic atrophy. In contrast to double-negative (DN) and single-positive (SP) thymocytes, most DP thymocytes (CD69(-)) do not constitutively express the IL-21 receptor (IL-21R). Accordingly, CD69(-) DP thymocytes from PBS-treated mice were unresponsive to IL-21 administration. However, following GC injection, surviving CD69(-) DP thymocytes up-regulated IL-21R and responded to IL-21 treatment as evidenced by enhancement of Bcl6 expression and phosphorylation of STAT1, STAT3 and STAT5. Consequently, IL-21 administration to GC-treated mice accelerated thymic recovery by expanding considerably DP thymocytes and, to a lesser extent, DN thymocytes. However, IL-21-induced expansion of DN/DP thymocytes did not alter the diversity of the intrathymic or peripheral T-cell receptor (TCR) repertoire. We conclude that IL-21 dramatically accelerates recovery from GC-induced thymic atrophy.